Pengaruh Pengungkapan Corporate Social Responsibility (CSR) dan Kinerja Keuangan Perusahaan terhadap Cumulative Abnormal Return (CAR) (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2010-2011) - Restu Cinthya Ayu; Istianingsih Sastrodiharjo (STIE Indonesia Banking School, 2015)
This study aims to examine the influence of corporate social responsibility disclosure and financial performance of the company to the cumulative abnormal return (CAR). The disclosure of social responsibility will be measured by Corporate Social Disclosure Index (CSDI), the financial performance is proxied to the return on equity (ROE), and the cumulative abnormal return (CAR) is a Cumulative Stock Return from April 2011 until March 2013. The analyzed database is a secondary database, which in time series form of manufacturing company in period year from 2010 until 2011. The result of statistical test shows that the corporate social responsibility has a positive and significant impact on ROE, and also ROE have positive effect on Cumulative Abnormal Return (CAR). But, the influence of corporate social responsibility to the cumulative abnormal return (ROE) is rejected.